THE RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE AND ATTITUDE AND THE INCIDENCE OF STUNTING IN TODDLERS - Ruminem, Ruminem; Sari, Rita Puspa; Widiastuti, Ida Ayu Kade Sri; Pratiwi, Fitri Diah (Fakultas Kedokteran, 2026)
Background: The occurrence of stunting in toddlers remains a major nutritional problem in Indonesia. One of the contributing factors to this high prevalence is the low level of knowledge, poor attitudes, and inadequate practices regarding nutritional intake. Objective: This study aims to determine the relationship between maternal knowledge and attitudes and the incidence of stunting among children in the working area of the Juanda Public Health Center, Samarinda City.Methods: This study utilized a cross-sectional approach. The sample consisted of 78 mothers with toddlers in the working area of the Juanda Public Health Center, Samarinda, selected using a purposive sampling technique. The research instruments included questionnaires and stunting assessment indicators based on Z-scores. The collected data were analyzed using univariate and bivariate analysis with the chi-square test. Results: The findings showed that the majority of mothers had a good level of knowledge about stunting, accounting for 49 respondents (62.8%). Most mothers demonstrated a positive attitude toward stunting, totaling 68 respondents (87.2%). Furthermore, the majority of the toddlers did not experience stunting, comprising 53 children (63.7%). The chi-square test results revealed a significant relationship between maternal knowledge and the incidence of stunting in toddlers (p value = 0.015), as well as a significant relationship between maternal attitude and the incidence of stunting (p value = 0.000) Conclusion: The incidence of stunting in toddlers is significantly associated with maternal knowledge and attitudes regarding stunting. Continuous education on stunting prevention is crucial to enhance maternal understanding and awareness in mitigating stunting occurrences among toddlers.